2022
DOI: 10.1111/his.14804
|View full text |Cite
|
Sign up to set email alerts
|

Identifying recurrences and metastasis after ductal carcinoma in situ (DCIS) of the breast

Abstract: Identifying recurrences and metastasis after ductal carcinoma in situ (DCIS) of the breast Ductal carcinoma in situ (DCIS) of the breast is a non-invasive tumour that has the potential to progress to invasive ductal carcinoma (IDC). Thus, it represents a treatment dilemma: alone it does not present a risk to life, however, left untreated it may progress to a life-threatening condition. Current clinico-pathological features cannot accurately predict which patients with DCIS have invasive potential, and therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…Previous studies have indicated that ER expression in DCIS is associated with disease recurrence ( 7 , 8 ). Here, we found that DCIS fibroblasts enhanced DCIS.com growth and invasion in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have indicated that ER expression in DCIS is associated with disease recurrence ( 7 , 8 ). Here, we found that DCIS fibroblasts enhanced DCIS.com growth and invasion in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…For IDC fibroblasts, we considered molecular subtype and disease stage as potential factors for their heterogeneity. The effects of molecular subtype in gene expression have previously been documented ( 7 , 42 44 ). By PCA, fibroblasts that originated from triple negative IDC, such as 8661 and 2760 grouped more closely together than fibroblasts 8870 and 8727, which originated from ER+/PR/HER2+ IDC tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Professor Stephen Fox and his colleagues summarise the current knowledge of ductal carcinoma in situ (DCIS) and discuss in depth the relevant prognostic clinic‐pathological features to predict which types of DCIS have invasive potential, hence quantifying the risk of progression for individual patients who can avoid potential over‐ or under‐ treatment 9 . Future research directions are also highlighted.…”
Section: Updates On Diagnostic Entitiesmentioning
confidence: 99%